2018
DOI: 10.1080/10410236.2018.1437524
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Ebola Panic: Newspaper and Social Media Coverage of the 2014 Ebola Health Crisis

Abstract: During times of hot crises, traditional news organizations have historically contributed to public fear and panic by emphasizing risks and uncertainties. The degree to which digital and social media platforms contribute to this panic is essential to consider in the new media landscape. This research examines news coverage of the 2014 Ebola crisis, exploring differences in presentation between newspaper coverage and news shared on the social news platform Reddit. Results suggest that news shared on Reddit ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 20 publications
1
61
0
8
Order By: Relevance
“…2,3 On 30 September 2014, after the first laboratory-diagnosed Ebola virus was diagnosed in the United States, a media firestorm erupted with constant updates of the Ebola 'crisis'. 4 The public anxiety and panic ensued after the report was frequently attributed to the media's dramatized and sensational coverage. 5 Subsequently, media reports from unauthorized sources during the ongoing monkeypox outbreak in Nigeria were sensationalized and led to increased anxiety in the population.…”
Section: Letter To the Editor: Headline Stress Disorder Caused By Netmentioning
confidence: 99%
“…2,3 On 30 September 2014, after the first laboratory-diagnosed Ebola virus was diagnosed in the United States, a media firestorm erupted with constant updates of the Ebola 'crisis'. 4 The public anxiety and panic ensued after the report was frequently attributed to the media's dramatized and sensational coverage. 5 Subsequently, media reports from unauthorized sources during the ongoing monkeypox outbreak in Nigeria were sensationalized and led to increased anxiety in the population.…”
Section: Letter To the Editor: Headline Stress Disorder Caused By Netmentioning
confidence: 99%
“…The "risk-as-feeling" model and affect heuristics show that the cognitive system (risk assessment) interacts with the emotional system, and then affects behavior. Previous studies have proved that media framing highlights risks and consequently leads to public panic [50]; nevertheless, studies also have demonstrated that the mass media (especially the official mainstream media) pay increasing attention to risk communication, and curb a health crisis to reduce public panic by emphasizing solutions and successful containment measures [51]. Undoubtedly, it has become a form of appeasement and a tool to eliminate panic [52].…”
Section: Negative Emotionsmentioning
confidence: 99%
“…The objective of this analysis is to determine whether exposure to social and traditional (radio, TV, and newspaper) media during the rise of the COVID-19 pandemic was associated with mental distress among U.S. adults. Given the evidence that exposure to social and traditional media may have differential associations with mental distress, 14,22 these sources are examined separately. In addition, because depressive symptoms have been associated with greater social media use, 23,24 this study tests whether associations were moderated by prior depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%